2016
DOI: 10.1210/en.2016-1235
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNAseq Reveals That Pancreatic β-Cells From Very Old Male Mice Have a Young Gene Signature

Abstract: Aging improves pancreatic β-cell function in mice. This is a surprising finding because aging is typically associated with functional decline. We performed single-cell RNA sequencing of β-cells from 3- and 26-month-old mice to explore how changes in gene expression contribute to improved function with age. The old mice were healthy and had reduced blood glucose levels and increased β-cell mass, which correlated to their body weight. β-Cells from young and old mice had similar transcriptome profiles. In fact, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…This could indicate differences between rodent and human beta-cells, but could also be due to the specific time window covered in our study. We found that 34 genes with significantly lower expression in beta-cells from very old mice compared to 3-month-old mice (Xin et al, 2016) also decreased in expression in our maturation time course. Among these shared genes were the TFs Srf , Jun , Fos, Nr4a1, Fosl2 , and Fosb , suggesting that expression of these TFs continues to decrease as beta-cells age.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…This could indicate differences between rodent and human beta-cells, but could also be due to the specific time window covered in our study. We found that 34 genes with significantly lower expression in beta-cells from very old mice compared to 3-month-old mice (Xin et al, 2016) also decreased in expression in our maturation time course. Among these shared genes were the TFs Srf , Jun , Fos, Nr4a1, Fosl2 , and Fosb , suggesting that expression of these TFs continues to decrease as beta-cells age.…”
Section: Discussionsupporting
confidence: 48%
“…2B). To further validate the time ordering method, we projected published RNA-seq data from single beta-cells of 3-month-old mice (Xin et al, 2016) onto our pseudotemporal trajectory and found that the median of these cells correctly projected at the end of the pseudotime spectrum (see Suppl. Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three research groups have described heterogeneity in the beta cell population with particular gene signatures driving such differences (Baron et al, 2016; Muraro et al, 2016; Segerstolpe et al, 2016). However, Xin et al (2016b) were not able to detect such diverse cell types. Several reasons could account for these discrepancies.…”
Section: Molecular Heterogeneitymentioning
confidence: 83%
“…To begin to lay the foundation for studying beta cells at the molecular level, two approaches have been undertaken: an unbiased analysis of gene expression through single cell RNA sequencing, and the separation of beta cells into groups that differ in their protein expression. Although there are caveats associated with single cell RNA sequencing approaches (Xin et al, 2016a), several studies have provided important new insights into beta cell biology (Bader et al, 2016; Baron et al, 2016; Dorrell et al, 2016; Li et al, 2016; Muraro et al, 2016; Segerstolpe et al, 2016; Wang et al, 2016; Xin et al, 2016b). The separation of cells based on protein expression has also resulted in the discovery of several molecular markers ranging from cell-surface proteins to intracellular molecules involved in metabolism that are differentially expressed in a beta cell subpopulation or denote a particular metabolic state ( Figure 1 ) (Pipeleers, 1987; Jetton and Magnuson, 1992; Kiekens et al, 1992; Giordano et al, 1993; Heimberg et al, 1993; Jorns et al, 1999; Guz et al, 2001; Johnson et al, 2006; Bosco et al, 2007; Hermann et al, 2007; Saisho et al, 2008; Wang et al, 2008, 2016; Karaca et al, 2009; Szabat et al, 2009; Smukler et al, 2011; Katsuta et al, 2012; Bader et al, 2016; Beamish et al, 2016; Dorrell et al, 2016).…”
Section: Molecular Heterogeneitymentioning
confidence: 99%